Продовження робіт на селищі Ходосівка-Рославське на Київщині - Готун, І.А.; Сухонос, А.М.; Казимір, О.М. (Археологічні дослідження в Україні, 2009)
The publication is devoted to the results of research of an extraordinary Ancient Rus settlement Khodosivka-Roslavske of Khodosivka archaeological complex. Despite the small area, quite interesting materials describing various aspects of life of the ancient habitants of the settlement have been discovered. Unexpected was the record of a goldsmith’s workshop where amber jewelry were made.